Hybrid Threats: A new menace in International Era and the Presence of Russia in the Balkan Peninsula - Τούμπανη, Μαργαρίτα-Γεωργία (Πανεπιστήμιο Πελοποννήσου, 2019)
This dissertation addresses a questions’ set; what a hybrid threat is? Does Russia has hybrid strategy and if yes, which are its characteristics? Does Russia applies such strategy against the Balkans? The main research problem, in which the question is referred, is the delimitation of hybrid threats and Russia’s hybrid strategies in the Balkans. The methodology we are going to follow is the qualitative method, using references from the theory of international relations, the field of strategic studies, geopolitics and history. In the essay after the definition of hybrid threat, we argue that Russia has hybrid strategy, by analyzing it and by giving recent examples. In the first chapter we analyze and clarify the term “hybrid threat”, in the second, Russia’s hybrid strategy in theory and in the third some cases of Russia’s hybrid strategy in the Balkans. In the section of conclusions, there are the results of the findings and author’s opinion.
Keywords: Βαλκανική Χερσόνησος--Εξωτερικές σχέσεις--Ρωσία; Ρωσία--Εξωτερικές σχέσεις--Βαλκανική Χερσόνησος; Γεωπολιτική; Πόλεμος; Υβριδικές απειλές; Υβριδικός πόλεμος; Ρωσία; Βαλκάνια; Στρατηγική